2005
DOI: 10.1029/2005gl024327
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the origins of interannual thermocline variations in the tropical Indian Ocean

Abstract: Based on the data analysis of the 1000 hPa wind, SST and SSH anomalies, it is revealed that the atmospheric variations associated with Indian Ocean Dipole (IOD, or referred as Indian Ocean Zonal Dipole Mode, IOZDM) consist of a pair of anticyclones closely north and south of the equator with accompanying intense equatorial easterly anomalies, while the atmospheric variations related to El Niño/Southern Oscillation (ENSO) include a strong anticyclone in the southeastern tropical Indian Ocean (TIO) at higher lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
145
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 165 publications
(160 citation statements)
references
References 22 publications
14
145
1
Order By: Relevance
“…Chambers et al [1999] and Xie et al [2002] demonstrated that the STIO subsurface variations are mainly associated with ENSO forcing, while Rao and Behera [2005] showed that Rossby waves formed in the region 5 S-10 S are largely due to IOD. Yu et al [2005] showed that the Rossby waves associated with IOD dominate north of 10 S while ENSO forcing dominates south of 10 S. In the cooccurrence years, the southwest TIO shows a strong and sustained warming due to strong downwelling Rossby waves [Chakravorty et al, 2013]. However, the mechanisms for the generation/maintenance of these Rossby waves during the cooccurrence years are not yet clearly understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chambers et al [1999] and Xie et al [2002] demonstrated that the STIO subsurface variations are mainly associated with ENSO forcing, while Rao and Behera [2005] showed that Rossby waves formed in the region 5 S-10 S are largely due to IOD. Yu et al [2005] showed that the Rossby waves associated with IOD dominate north of 10 S while ENSO forcing dominates south of 10 S. In the cooccurrence years, the southwest TIO shows a strong and sustained warming due to strong downwelling Rossby waves [Chakravorty et al, 2013]. However, the mechanisms for the generation/maintenance of these Rossby waves during the cooccurrence years are not yet clearly understood.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, in cooccurrence years the southwest TIO displays strong and sustained warming due to the presence of downwelling Rossby waves. According to the previous studies [Rao and Behera, 2005;Yu et al, 2005], wind stress curl associated with IOD events are responsible for westward propagating downwelling Rossby waves. Figure 1 illustrates the time-longitude composite of SSH and wind stress curl anomalies at different latitudinal belts for pure El Niño (left), cooccurrence (middle), and pure IOD (right) years.…”
Section: Observed Interannual Variability In the Stio Rossby Wavesmentioning
confidence: 99%
“…This downwelling Rossby wave propagates westward and suppresses the upwelling in the thermocline dome (e.g. Masumoto and Meyers 1998;Yu et al 2005). Through this mechanism, the SWIO SST warms up and persists to the summer even as El Niño decays (Xie et al 2002).…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 99%
“…For the POST epoch, thermocline depressions begin to develop and amplify in the eastern half of the basin during September(0) to December(0) in response to in situ downwelling Ekman pumping. The Ekman pumping is associated with an anomalous anticyclone that develops over the southeast TIO during the developing phase of El Niñ o and/or the Indian Ocean dipole (IOD) Yu et al 2005;Rao and Behera 2005). [The IOD is the zonal mode of the equatorial Indian Ocean involving Bjerknes feedback (Saji et al 1999;Webster et al 1999). ]…”
Section: Indian Ocean Responsementioning
confidence: 99%